Biphosphonate-related osteonecrosis of the jaw in an old patient with oral bisphosphonate exposure - Aiex, Leticia Simao (2015)
Polypharmacy is defined as consumption of five or more concomitant drugs over a period of time, and its incidence is more common in people aged over 65 years. Osteoporosis is the most frequent metabolic bone disease in Western countries and the second most frequent health problem worldwide after cardiovascular diseases. Its main complication is fracture caused by bone fragility, and it affects more women than men. Various treatments are available to prevent them, and one of the most commonly used treatments is bisphosphonate therapy. These drugs are widely used as first-line therapy, especially in postmenopausal osteoporosis. Although biphosphonates are generally well tolerated, they are not free of side effects, and one of the most serious ones is osteonecrosis of the jaw, as shown in the following clinical case. For these and other reasons, it is always important to perform risk-benefit analysis individually before starting any treatment, especially in patients with polypharmacy.